2020
DOI: 10.1093/bib/bbaa124
|View full text |Cite
|
Sign up to set email alerts
|

DeepTorrent: a deep learning-based approach for predicting DNA N4-methylcytosine sites

Abstract: Abstract DNA N4-methylcytosine (4mC) is an important epigenetic modification that plays a vital role in regulating DNA replication and expression. However, it is challenging to detect 4mC sites through experimental methods, which are time-consuming and costly. Thus, computational tools that can identify 4mC sites would be very useful for understanding the mechanism of this important type of DNA modification. Several machine learning-based 4mC predictors have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 48 publications
0
60
0
Order By: Relevance
“…It should be noted that we tried a large number of other types of features generated by iLearn [36] or Pse-in-One [37] toolkits when we designed the input features (data not shown). The sequence-based features generated by these two toolkits have been used widely for predicting both RNA post-transcriptional modification sites [38][39][40] and post-translational modification sites [41,42]. Our experimental results demonstrated that our proposed feature combination in this study yielded satisfactory performance, which cannot be significantly improved when they were combined with other features.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that we tried a large number of other types of features generated by iLearn [36] or Pse-in-One [37] toolkits when we designed the input features (data not shown). The sequence-based features generated by these two toolkits have been used widely for predicting both RNA post-transcriptional modification sites [38][39][40] and post-translational modification sites [41,42]. Our experimental results demonstrated that our proposed feature combination in this study yielded satisfactory performance, which cannot be significantly improved when they were combined with other features.…”
Section: Discussionmentioning
confidence: 89%
“…Eventually, they identified 41 bp as the optimal length for consistently obtaining the best performance, regardless of species. Surprisingly, the same optimal sequence length has been used in later studies 69 , 70 of other species. 24 , 25 Ultimately, a set of 3,108, 3,538, 3,956, 776, 1,812, and 1138 samples for C .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various 4mC sites identifiers have been suggested for several species entailing A. thaliana, C. elegans, D. melanogaster, G. pickeringii, E. coli and G. subterraneus [23,24]. Further a first computational tool for 4mC identification in Rosaceae genomes is recently introduced which is, i4mC-ROSE [25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, neural networks have acquired great importance due to their high performance in different fields like medical imaging [29][30][31], agriculture [32][33][34][35][36][37], image quality assessment and others. Moreover, neural networks have exhibited great performance in the identification of 6mA sites [38,39], m6A sites [40,41], 4mC sites [23,24,42], functional piRNAs [43], N4-acetylcytidine sites [44], promoters classification [45] and others. Inspired from the high performance given by neural network tools for modification identification in different sites, we have proposed a neural network based tool for 4mC identification in Rosaceae genomes.…”
Section: Introductionmentioning
confidence: 99%